Uspešnost tržnega komuniciranja na medorganizacijskih trgih - Jerman, Damjana (Akademija MM, 2009)
The composition of communication mix and the integration of the different instruments vary with time and also depend on type of product market (consumer or business-to-business). This paper focuses on a development and testing of the model of marketing communication effectiveness in the business-to-business market. Building on past research from the marketing communications and business-to-business marketing literatures, the model (which incorporates concepts of the source of communication, communication messages, marketing communications objectives, communication channels, target groups and two-way communications) is tested to examine the impact of these antecedent variables on marketing communications effectiveness. In addition to these relations, we investigated the relationship between effectiveness of marketing communications, and its result - the impact of marketing communication's effectiveness on the organizational performance, both in marketing, financial and other aspects. Structural model of the effectiveness of marketing communication was empirically tested on a sample of Slovenian companies, which operate in the business-to-business markets. We have confirmed the positive relationship between these constructs. The contribution provides a comprehensive point of view at the effectiveness of marketing communications as a consequence and a cause in the process of marketing communications.
Keywords: marketing; podjetja; poslovna strategija; trženje; tržno komuniciranje; uspešnost